Turnover Intention : A systematic literature review (SLR) - Febridiyanti, Hanindya; Herachwati, Nuri (Fakultas Ekonomi Universitas Kadiri, 2024)
The purpose of this research is to systematically review existing research regards Turnover Intention in organization. Besides, the purpose of writing this article is to find out the factors that cause Turnover, so that companies can anticipate and maintain existing human resources. Because the issue of Turnover Intention is a very big thing at this time also detrimental to the company such as loss. All articles that cited have been systematically review by author. Author filtered with quality of articles from Q1 until Q2, it will strengthen the validity and reliability of articles that will be reviewed. The findings from our study indicate that research using the Systematic Literature Review (SLR) method shows various variables that can support Turnover Intention. Antecedent variables that come from external factors, namely organization, culture, leadership and internal factors. In addition, there are mediating and moderating variables that can strengthen the relationship between antecedents and Turnover Intention, for example trust in supervisor, commitment, job embeddedness. The review has several limitations that require further research. Conduct research focused only on certain sectors, so that it will be more visible the appropriate culture to implement Turnover-related problem solving.